EVALUATION OF ACADEMIC MOTIVATION, A CASE STUDY OF ENG-LISH DEPARTMENT STUDENTS AT DUHOK UNIVERSITY. - SULAIMAN, MOHAMAD SALIH A.; MOUSA, SHILAN MAJEED (Journal of Duhok University, 2020)
ABSTRACT There is a vast body of literature that acknowledges an important relationship between motivation and academic performance. It confirms that motivation is crucial for learning, and it enhances academic performance among university students. This study reports the results of a survey exploring the students’ perceptions on the teaching practices in a two-semester course of English Syntax, considering the components of the MUSIC model of academic motivation elaborated by Jones (2009). For this purpose, we used the MUSIC inventory (College Student version) developed by Jones (2012) to measure constructs related to the five components of the MUSIC model (i.e., eMpowerment, Usefulness, Success, Interest, and Caring) that are critical to students’ motivation. That inventory has been shown to produce valid scores with samples of undergraduate students (Jones & Skaggs, 2016; Tendhar, 2015). The inventory was administered to 90 4th- year undergraduate students in the Department of English, College of Languages, University of Duhok, near the end of the second semester. They responded to the scale items in the MUSIC inventory by choosing one of six options on a Likert-format scale. The students’ ratings of the components and aspects of the course that influenced their perception on it are discussed. Also, researchers’ suggestions for improving the instructional design of the course from the perspective of the MUSIC motivational model are presented.